The economics of international transfers - Brakman, Steven 1957-; Marrewijk, Charles van 1959- (Cambridge Univ. Press, 1998)
This book discusses welfare effects, distortions, third parties, rent-seeking, the "trade or aid" discussion, multilateral agencies, tied aid and imperfect competition.
Keywords: Balance des paiements; Betalingsbalans; Internationale handel; Welthandel; Balance of payments; Zahlungsbilanz; Außenwirtschaftstheorie; Kapitaltransfer; Wirtschaftstheorie